2019
DOI: 10.1103/physrevaccelbeams.22.110705
|View full text |Cite
|
Sign up to set email alerts
|

Method for polarization shaping at free-electron lasers

Abstract: X-ray free electron lasers provide short, polarized, high-power pulses of x-ray radiation, where polarization properties are determined by the undulator magnetic field. We propose a cost-effective method to shape the polarization of FEL radiation on the sample both spatially, on a few-μm scale, and/or temporally on the 100-femtosecond scale. The method is based on coaxial superposition of two coherent radiation pulses with different frequencies emitted in two consequent undulators set to emit radiation with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Note that the high brightness of XFEL makes it possible to implement previously inaccessible methods of diffraction pattern imaging using photoelectrons [171], methods of nonlinear X-ray physics [172], and new techniques of radiation polarization control [173].…”
Section: Specific Features Of Xfel Imagingmentioning
confidence: 99%
“…Note that the high brightness of XFEL makes it possible to implement previously inaccessible methods of diffraction pattern imaging using photoelectrons [171], methods of nonlinear X-ray physics [172], and new techniques of radiation polarization control [173].…”
Section: Specific Features Of Xfel Imagingmentioning
confidence: 99%
“…Furthermore, the method could be combined with other methods. For example, consideration of temporal or short pulse effects can be envisaged that alter the FSL in the temporal domain (e.g., [47]) adding a further dimension for potential experimental exploitation.…”
Section: Discussionmentioning
confidence: 99%
“…[213][214][215][216][217] The study of complex vector fields is not restricted to photons, as is shown by recent advances in vector neutron 218 and electron beams. 219,220 We strongly suspect that vector fields have a long -and potentially twisted -future.…”
Section: Discussionmentioning
confidence: 99%